O25 Immediate effects of ankle taping on joint stiffness and joint angle of the lower extremity during a drop landing. (17th September 2017) - Jun, H; Baker, R; Chun, YM; Kim, JA; Lee, SY
Abstract : Study Design: Control study. Objectives: To investigate effects of ankle taping on changes in biomechanics of the lower extremity during drop landing. Background: Clinicians often utilise ankle tapings to prevent ankle sprains during practice/competition. Though ankle tapings are regularly employed, the effect of tape application on lower extremity biomechanics is not fully known. Methods and Measures: Twenty-eight participants (14 healthy, 14 with chronic ankle instability [CAI]) performed drop landings from a box of 60 cm height (3 before and 3 after traditional ankle taping application). An infrared optical camera system (Vicon Motion Systems Ltd. Oxford, UK) and force-plate (AMTI, Watertown, MA) collected kinematic and kinetic data during drop landing. Stiffness and sagittal angle of the ankle, knee, and hip between initial contact (IC) and maximum knee flexion angle were analysed. Results: Sagittal angle of ankle was statistically decreased [Healthy: p<0.05; M±SD: 56.38±55.56(pre), 49.31±5.30(post); CAI: p<0.05; M±SD: 53.12±7.08(pre), 47.68±6.85(post)], while sagittal angles of the knee [Healthy: p>0.05; M±SD: 53.43±8.21(pre), 52.68±7.92(post); CAI: p>0.05; M±SD: 53.26±7.47(pre), 55.16±9.40(post)]and hip [Healthy: p>0.05; M±SD: 30.00±8.62(pre), 30.42±9.16(post); CAI: p>0.05; M±SD: 29.42±6.30(pre), 31.10±7.13(post)] were not significantly changed after taping. Significant decreases in hip stiffness [Healthy: p<0.05; M±SD: 1442.49±413.34(pre), 1113.76±460.90(post); CAI: p<0.05; M±SD: 1313.78±420.54(pre), 1033.33±309.16(post)] and knee stiffness [Healthy: p<0.05; M±SD: 273.09±57.59(pre), 210.02±78.09(post); CAI: p<0.05; M±SD: 244.05±69.85(pre), 201.07±68.74(post)] were found, while ankle stiffness was significantly increased [Healthy: p<0.05; M±SD: 56.38±5.56(pre), 49.31±5.30(post); CAI: p<0.05; M±SD: 53.12±7.08(pre), 46.04±7.97(post)] post-tape application. Conclusions: Ankle taping reduces ankle joint angle in a sagittal plane during drop landing and increases ankle stiffness, while also reducing proximal joint stiffness. These findings indicate possible changes in the shock absorption mechanism during landing following ankle tape. Therefore, clinicians may need to consider potential changes in proximal joint movement strategies to attenuate shock during landing following ankle tape application and how this may impact athletic performance or injury risk.